Analysis of Regional Employment Dynamics Using a Spatially Modified Shift-Share Model: The Case of the Chorotega Region, 1990–2009 - Arias Ramírez, Rafael (2011)
The article we are presenting results from the research project entitled Analysis of Territorial Competitiveness and Labor Market in the Chorotega region, which is part of the research program in regional economics we have been conducting at the Institute for Economic Research (IICE) of the Universidad de Costa Rica (IICE) since the year 2005 This study explores the regional dynamics of employment in the Chorotega region in the period of time between1990-2009 By using the Shift Share analysis, in both, the classic and spatially modified formulations, we were able to divide employment growth in four effects: the national effect, the sectorial effect, the regional effect and the locational effect.